Cylinder seals from Tūlūl Al-Baqarat Technical study (Journal of Studies in History and Archeology, 2022)
The seal isa solid piece of clay,stone,metal or any other organic matter.Seals on tow flat and cylinder types.the desired scene is carried out by digging on the surfaceof the seal with sunken sculpture invertedly. When printed on clay, the executed scene appears prominently and correctly, often the seal contains a hole to hang it.theseal is used a lot in daily life, as wellas its importance in archaeological studies.